Effects of foliar spray of NAA, 2,4-D and urea on fruit yield and quality of Citrus limon (L.) Burm. cv. Assam lemon - Senjam, Bidyarani Devi; Singh, SR (Bangladesh Journal of Botany, 2021)
Effects of foliar spray of NAA, 2, 4-D and urea on fruit yield and quality of Citrus limon (L.) Burm. cv. Assam lemon was studied. Nine treatments were imposed in RBD for two seasons (summer and winter). Among the treatments in T6 (NAA @ 20 ppm + 2,4-D @ 20 ppm + 1% urea) the maximum pulp content (81.58 g/fruit), juice content (40.47 ml/fruit), reducing sugar (0.51%) and ascorbic acid (48.56 mg/100 g) were recorded. Whereas, maximum TSS (9.88%), total sugar (1.66%) with minimum titratable acidity (3.10%) was recorded in treatment T5 (NAA @ 10 ppm + 2,4-D @ 10 ppm + 1% urea). Hence, the combination of recommended dose of fertilizers 100 : 100 : 100 g NPK/plant/year along with 20 kg FYM and NAA @ 20 ppm + 2,4-D @ 20 ppm + 1% urea foliar spray twice (after fruit setting and fully developed stage) may be recommended for improvement of yield and quality of this main cultivar lemon for the North East region of India in the future.